Research in Education from a multicultural perspective: a study on anti-racist practices in a continuing teacher training extension course (Práxis Educativa, 2024)
This article aims to discuss research in education from a multicultural perspective, illustrating the issue from a case study with moments of action research in an extension course that presents possibilities and challenges of anti-racist teacher continuing education, from a qualitative perspective. Education for ethnic-racial relations is elucidated, with emphasis on the trajectory and objectives of Federal Law no. 10.639/2003, an important milestone in the restructuring of educational practices based on the valuing of African and Afro-Brazilian history and culture with a focus on collectivity and equality. Reflecting on the expectations of the students, described in the letters of intent to join the course, the relevance of the teaching aptitude for anti-racist and multicultural practice is identified. The article points to the recognition and respect for diversity and to the confrontation of structural racism, raising considerations about the importance of continuing teacher training.Keywords: Research in education. Continuing teacher training. Anti-racism. Multiculturalism.